Identification of reproductive stages of Jatropha mollissima (Pohl) Baill. for adaptation and coding according to the BBCH scale - Rabbani, Allívia Rouse Carregosa (2023)
The species Jatropha mollissima (Pohl) Baill., which according to the literature, exhibits antioxidant, antibacterial, and antiproliferative properties, requires studies to characterize its phenology, particularly flowering and fruit ripening, to better understand its development and optimize its production system and utilization. Considering that the Biologische Bundesanstalt, Bundessortenamt und Chemische Industrie (BBCH) scale, which standardizes the description of plant phenological stages, has not yet been applied to J. mollissima, this article aims to describe the BBCH codes in a way that best adapts them to the specific characteristics of this species. The phenological events of the species were described in 4 main stages according to the general scale: 5 (Inflorescence emergence), 6 (Flowering), 7 (Fruit development), and 8 (Fruit ripening). Based on this, 14 sub-stages were described: 51 (Visible inflorescence), 55 (Visible floral buds), 56 (Sepals covering half of the corolla), 59 (First visible flower petals), 60 (First open flowers), 65 (Petals and anthers start to fall), 71 (Visible cluster of fruits), 72 (Fruit reaches 20% of its size), 73 (Fruit reaches 50% of its size), 79 (Fruit reaches its final size), 81 (Initiation of maturation), 85 (Advanced ripening and beginning of epicarp detachment), 87 (Advanced ripening and almost detached epicarp), and 89 (Ripe fruit). This expanded scale provides a valuable tool for the development of phenological models to enhance our understanding, domestication, and improvement of this oilseed crop.